Assessing leadership styles of coaches and testing the augmentation effect in sport - Gomes, António Rui (2014)
This chapter proposes an instrument to evaluate leadership styles in three domains (e.g., transformational, transactional, and decision-making leadership) and test the augmentation effect of these domains on the explanation of satisfaction with leadership and coach-athlete compatibility. In total, 348 male athletes who play futsal and soccer were recruited. We evaluated leadership styles, satisfaction with leadership, and coach-athlete compatibility. The confirmatory factor analysis demonstrated acceptable fit levels for the organization of the leadership scales with second-order factors of transformational leadership and two correlated factors for transactional and decision-making leadership. Confirmatory factor analysis also point out acceptable fit levels for the measures of satisfaction with leadership and coach-athlete compatibility. The hierarchical regression analysis indicated the predictive value of the leadership domains for explaining satisfaction with leadership (61% of variance explained) and coach-athlete compatibility (50% of variance explained). We found partial support for the validity of the leadership scale and confirmed the augmentation effect.